APAKAH TINGKAT SUKU BUNGA SERTIFIKAT BANK INDONESIA MAMPU MEMODERASI DETERMINAN YIELD TO MATURITY? - Maryanti, Eny (2021)
This study aims to determine the factors that effect the yield to maturity with interest rate of Indonesia Bank Certificates as a moderating effect on all companies listed on the Indonesia Stock Exchange. Previous research shows different results, it is necessary to do research again to test the effect of the four variables on yield to maturity of bond by adding moderating variables. The population of this study is 121 bond were recorded and traded on the Indonesian Stock Exchange in the 2016-2018 period. Based on the purposive sampling criteria is 15 companies with a total of 45 bond issued in the 2016-2018 period were obtained. The result of this study used the SmartPLS (Partial Least Square) data analysis test. Interest rate of Indonesian Bank as a pure moderator variable on the effect of company size on yield to maturity. Interest rate of Indonesian Bank as a homologiser moderator on the effect of bond ratings, debt to equity ratio, and financial leverage on yield to maturity.